Measuring collaborative synergies with advanced real options: MNEs' sequential acquisitions of international ventures - Andrejs Čirjevskis (Journal of Risk and Financial Management, 2023)
This paper aims to extend the real options theory valuing strategic collaborative synergies by advanced real options with changing volatility and contributes to the international business literature on MNEs' sequential acquisitions of international ventures. The proposition is that collaborative synergies can be valued with advanced real options with changing volatility when an MNE is pursuing the sequential acquisition of an international venture and the MNE's stock volatility is changing at the time of deciding on a full takeover. The paper discusses how recombining and non-recombining lattices with constant and changing volatilities can be employed to value the collaborative synergies of sequential international acquisitions. The theoretical proposition has been justified with the explanatory case study: Natura Cosméticos S.A.'s (Brazil) sequential acquisition of the Aesop brand (Australia). In conclusion, the paper discusses its findings, contributions, limitations, and future work.
Keywords: 650; international strategy; synergy; acquisition; real options